Relaxase MobM Induces a Molecular Switch at Its Cognate Origin of Transfer - Lorenzo-Díaz, Fabián; Fernández-López, Cris; Guillén-Guío, Beatriz; Bravo, Alicia; Espinosa, Manuel (Frontiers in Molecular Biosciences, 2018)
The MOBV1 family of relaxases is broadly distributed in plasmids and other mobile genetic elements isolated from staphylococci, enterococci, and streptococci. The prototype of this family is protein MobM encoded by the streptococcal promiscuous plasmid pMV158. MobM cleaves the phosphodiester bond of a specific dinucleotide within the origin of transfer (oriT) to initiate the conjugative transfer. Differently from other relaxases, MobM and probably other members of the family cleaves its target single-stranded DNA through a histidine residue rather than the commonly used tyrosine. The oriT of the MOBV1 family differs from other well-known conjugative systems since it has sequences with three inverted repeats, which were predicted to generate three mutually-exclusive hairpins on supercoiled DNA. In this work, such hypothesis was evaluated through footprinting experiments on supercoiled plasmid DNA. We have found a change in hairpin extrusion mediated by protein MobM. This conformational change involves a shift from the main hairpin generated on ‘naked’ DNA to a different hairpin in which the nick site is positioned in a single-stranded configuration. Our results indicate that the oriTpMV158 acts as a molecular switch in which, depending on the inverted repeat recognized by MobM, pMV158 mobilization could be turned ‘on’ or ‘off’.